2018
DOI: 10.1177/0300060517751740
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diverticulosis and nonalcoholic fatty liver disease in elderly patients

Abstract: ObjectiveTo compare clinical and laboratory features of elderly patients with and without diverticulosis and assess factors related to hepatosteatosis.MethodThis retrospective case–control study analysed the clinical and laboratory data, colonoscopy and abdominal ultrasonography records of patients >65 years who underwent colonoscopies. Subjects were categorized according to the presence and absence of colonic diverticulosis. Univariate/multivariate logistic regression analyses were performed to evaluate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…To determine the composition of the experimental slag system at 1873 K, the pseudo‐hexahydric phase diagram of FeO−SiO 2 −Cr 2 O 3 −CaO (10 wt%)−TiO 2 (10 wt%)−MnO (12 wt%) at an oxygen partial pressure of 10 −8 was calculated using FACTSage 7.0 based on the compositions of the samples, using the normalized method, [ 28–30 ] and A1−A5 corresponded to S1–S5, as shown in Figure 4 . The solid–liquid ratio of the slag decreased from 21.5% to 1.9% when the FeO content decreased from 37 to 11 wt%, calculated using the Equilib Module in FACTSage 7.0, [ 31 ] consistent with the XRD and SEM results. Considering the extremely limited thermodynamic data available for V, the pseudo‐hexahydric phase diagram does not exhaustively reflect the experimental slag system; however, it provides a relatively accurate phase distribution for the complex slag system.…”
Section: Resultssupporting
confidence: 60%
“…To determine the composition of the experimental slag system at 1873 K, the pseudo‐hexahydric phase diagram of FeO−SiO 2 −Cr 2 O 3 −CaO (10 wt%)−TiO 2 (10 wt%)−MnO (12 wt%) at an oxygen partial pressure of 10 −8 was calculated using FACTSage 7.0 based on the compositions of the samples, using the normalized method, [ 28–30 ] and A1−A5 corresponded to S1–S5, as shown in Figure 4 . The solid–liquid ratio of the slag decreased from 21.5% to 1.9% when the FeO content decreased from 37 to 11 wt%, calculated using the Equilib Module in FACTSage 7.0, [ 31 ] consistent with the XRD and SEM results. Considering the extremely limited thermodynamic data available for V, the pseudo‐hexahydric phase diagram does not exhaustively reflect the experimental slag system; however, it provides a relatively accurate phase distribution for the complex slag system.…”
Section: Resultssupporting
confidence: 60%
“…[1,2] It has been reported that about 600 million tons of copper were produced during the past two hundred years, of which around 20 pct was produced by Outotec flash smelting technology. [3] However, because of continuous depletion of ore-based copper mineral resources, as well as tighter environmental regulations and stronger demands for actions towards circular economy, [4] secondary copper resources such as industrial copper scrap and waste electrical and electronic equipment (WEEE) are increasingly being regarded as important copper resources.…”
Section: Introductionmentioning
confidence: 99%
“…This study reported that moderate and severe fatty liver disease, as well as waist-hip ratio, were risk factors for ADD, highlighting the possible role of central obesity and NAFLD in the pathogenesis of ADD [18]. Contrary to these findings, Sahin et al [21] found that in elderly patients, diverticulosis is a negative predictor of liver steatosis. According to this study, diverticulosis could be an indirect sign of malnutrition in patients over 75 years of age, since higher values of albumin and triglycerides, were identified as independent predictors of liver steatosis [21].…”
Section: The Impact Of Nafld and Colonic Diverticulosis On Metabolic Syndromementioning
confidence: 58%
“…Contrary to these findings, Sahin et al [21] found that in elderly patients, diverticulosis is a negative predictor of liver steatosis. According to this study, diverticulosis could be an indirect sign of malnutrition in patients over 75 years of age, since higher values of albumin and triglycerides, were identified as independent predictors of liver steatosis [21]. The age difference between the patients included in these studies may be the reason for these conflicting findings.…”
Section: The Impact Of Nafld and Colonic Diverticulosis On Metabolic Syndromementioning
confidence: 84%
See 1 more Smart Citation